Modelagem das curvas de rendimento de turbinas aeronáuticas turbofan e turbojato - Maschietto, Victor Camilo Levartoski (2014)
Gas turbines are heat engines widely used for electric power generation and aircraft propulsion. This work aimed to make mathematical simulations to obtain the main curves of the operational parameters of turbojet and turbofan aeronautical turbine types, based on the ideal thermodynamic cycle. The curves were modeled using the EES® software, in order to have the determination of the thrust behavior, specific fuel consumption, thermal efficiency, propulsive efficiency and overall efficiency in function of the air pression ratio, Mach number and bypass ratio. Once the performance curves of the ideal engines were obtained, comparisons between the two types of engines were made and the deviations of the modeling concerning experimental results available on literature were verified. For the turbojet type, differences close to 20% between real values and the ideal modeling were observed, for the specific thrust and specific fuel consume, while for the turbofan type, the difference between the ideal modeling and the real value of the specific thrust was close to 10%. The results show that the modeling of these turbines based on the ideal cycle, allows to obtain information of performance of turbojet and turbofan aeronautical motors fairly close to the experimentally obtained. The modeling showed that turbofan type deviates more from optimal conditions when compared to the turbofan type, due to higher thermal irreversibilities generated in energy conversion of the fuel.